Improving Oral Health in Populations Affected by Natural Disasters: The Role of International Collaboration - Ameneh Marzban (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Natural disasters such as earthquakes, floods, and hurricanes have devastating effects on human societies. These events not only destroy infrastructure and physical resources, but also leave profound psychological and social impacts. A crucial yet often overlooked aspect of these disaster scenarios is the oral health of the affected individuals.